Coronavirus disease 2019: fundamentals, chronology and vaccine evolution. Issue 4 (4th October 2021) - Thirupathaiah, Yeruva; Chandel, Anuj Kumar
Abstract : : The coronavirus disease 2019 (COVID-19) is caused by a novel coronavirus, which is recognized as Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2). The recent pandemic caused by SARS-CoV-2 is a concern of major public health emergency globally. The virus is highly contagious, enters through nasopharyngeal route into lungs and infects respiratory tracts and later disseminate to other organs in the body. If body immune response fails to eliminate or over responds to infection in affected persons, the condition turns to severe acute respiratory syndrome or pneumonia, multiple organ failure, septic shock and finally end-up with life in critical cases. Currently, there are no antiviral drugs available to eradicate the complete infection and the only treatment available to patients with critical illness is providing oxygen supply through ventilators along with few antiviral and anti-inflammatory drugs to relieve from the symptoms. Recently developed COVID-19 vaccines are available to the public in several countries for protecting against SARS-CoV-2. Further, researchers are vigorously being focused on development of novel vaccines, recombinant interferons, monoclonal antibodies against virus, finding of antiviral drugs to block coronaviral specific structural proteins or multiplication in infected persons, drugs for suppression of over production of pro-inflammatory cytokines by the human body and disease mechanisms of virus. However, because of combined treatment strategies and reduced pathogenicity of SARS-CoV-2, the current mortality rate has been reduced to less than 1–1.5% globally from 5 to 6% of initial COVID-19 pandemic. Unfortunately, sudden increase in number of cases in several countries and evolution of new pathogenic strains of SARS-CoV-2 variants from existing strains make another challenging task both for public and scientific communities. Hence, public health officials are recommending public to continue social distancing, avoid contact with infected persons, isolation and quarantine of exposed persons till COVID-19 prevention is under control.